Reforma systemu własności oraz organizacji i zarządzania w PRL - Ratajczak, Klemens (Wydział Prawa i Administracji UAM, 1989)
In the introduction, the author points to a renewed revival of discussions on the economic reform. The discussions stress system and model aspects, especially the system of ownership, organization and management. The impulse for such discussions are, in the author's opinion, continuous instability of the economy, the growth of inflation and market imbalance as well as a threat of a decreased standard of living. Then, the author shows obstacles in the process of development of our economy. Among them he mentions the state monopoly as the most important impediment. The economically efficienc of the state monopoly does not stem from the very fact of its existence but from the fact that it was created by means of tools which have never belonged to the catalogue of the rules of rational economy. From the viewpoint of the rules of rational economy only the forms of ownership, organization and management which will prove to be economicallyefficient should be allowed. Meanwhile, state enterprises were created not because they were economically superior but because enterprises operating in other forms of ownership Were banned or reduced. In further part of his article the author concludes that the essence of socialism should be seen not in the forms of ownership, organization and management but in the degree of satisfying the needs of the society. The discrepancy between the essence of that political system and the praxis of its implementation was one of more important causes of social unrest and protests. The political system in which history has vested the task of quickening the pace of satysfying human needs should not refrain from observing economic instruments and laws, including those concerned with an unrestricted development of different forms of organization and management. Towards the end of his article, the author indicates that in order to achieve the efficiency of functioning of our socio-economic life it is necessary to reform not only the economy itself but also political and ideological spheres of life.. In particular, it is necessary to get rid of the hitherto binding principle of' the primacy of politics over economics.
The reform of the system of ownership, organization and management in the Polish People's Republic'